Implementation of Infant Massage Therapy to Increase Oxygen Saturation in Neonates: A Scoping Review - Jubaedah, Dede; Fitri, Siti Yuyun Rahayu Yuyun; Mardhiyah, Ai (Indonesian Journal of Global Health Research, 2024)
Stress and pain in premature babies can cause a decrease in oxygen saturation and changes in respiratory rate. Touch stimulation is one of the most advanced senses used by medical practitioners to soothe babies. Objective: This review aims to see the effectiveness of implementing infant massage therapy in increasing oxygen saturation in neonates. Method: A literature search was conducted on: PubMed, ScienceDirect, and CINAHL. The collected data is then extracted, synthesized, and presented as tables and narratives. The search strategy uses the keywords ("baby massage" OR "massage therapy") AND ("Neonatal") AND (Oxygen Saturation)). The articles used are from 2017 to 2023. Results: 757 neonates participated in 10 studies from 4 countries that met this review's criteria. The literature research design used was Quasi-experimental (n=4) and Randomized Controlled Trial (n=6). Conclusions: In this review, it was found that implementing massage therapy can increase the average percentage of oxygen saturation. This review also found that several studies agreed that massage therapy would be more effective when combined with the prone position. However, study results are still found to be inconsistent with these results. This may occur due to several factors including heterogeneity of implementation, differences in clinical conditions, and the lack of studies that specifically examine the effectiveness of implementing infant massage therapy on increasing oxygen saturation in neonates.